Cognitive culture studies - Hanenberg, Peter (UCP Press, 2025)
Cognitive Culture Studies aims at studying the relation between mind and culture and their mutual interdependence. The mind produces culture as much as it is shaped by it. How the mind reaches out to the world out there and how this world translates into meaning, this is the overall issue of this book. The eight chapters claim, examine and perform the possibility and necessity of intersecting the study of culture and cognition by introducing key concepts like ‘tacit knowledge’, ‘force dynamics’, ‘conceptual blending’ and ‘intramental translation’. They apply these concepts in the analyses of literary works, Walter Benjamin’s ninth thesis on history, the idea of Utopia and Christopher Columbus’ non-discovery of the New World, alluding in the last chapter to the practical consequences of tacit knowledge and intramental translation in the practice of intercultural communication.